You Cannot Choose Your Family: Sociological Ambivalence in the Hemodialysis Unit. (January 2015) - Wilson, Patricia M.; Reston, Jonathan D.; Bieraugel, Rebecca; Da Silva Gane, Maria; Wellsted, David; Offredy, Maxine; Farrington, Ken
Living with end-stage renal disease is challenging and requires a great deal of self-management, but little is known about the experiences of patients and staff around the subject. We held six focus groups in three hemodialysis units, each unit hosting 1 staff and 1 patient focus group. A total of 15 staff members and 15 patients participated. We employed thematic analysis using a priori and emerging codes. Five key themes emerged: challenges, enablers, complex balancing acts, good patient/bad patient, and the hemodialysis unit as a family. We explored the family metaphor further through the work of Bourdieu, but concluded that relationships in the hemodialysis unit most closely fit the concept of sociological ambivalence. We present an explanatory framework around inherent tensions characterizing relationships within the hemodialysis unit and highlight implications for facilitating self-management and developing collaborative approaches to care.